2002
DOI: 10.1002/1099-0682(200205)2002:5<1049::aid-ejic1049>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Stereochemistry and Ligating Properties of Tetraalkyl-Substituted Ethanedithioamides − Evidence for the Lowering of High-Energy Rotation Barriers under the trans Influence of Pt-σ-Bonded Aryl Groups

Abstract: The structural and coordinating properties of five tetrasubstituted tetraalkyldithioxamides (R4DTO) have been studied: tetraethyldithioxamide (Et4DTO, 1), tetrabenzyldithioxamide (Bz4DTO, 2), (E,E)‐N,N′‐dibenzyl‐N,N′‐diethyldithioxamide [(E,E)‐Bz2Et2DTO, 3], (E,Z)‐N,N′‐dibenzyl‐N,N′‐diethyldithioxamide [(E,Z)‐Bz2Et2DTO, 4], (Z,Z)‐N,N′‐dibenzyl‐N,N′‐diethyldithioxamide [(Z,Z)‐Bz2Et2DTO, 5]. The solid structure of 4, determined by single‐crystal X‐ray diffraction, is characterised by two planar thioamide groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This bond length is therefore increased by approximately 0.113 Å through the trans labilizing influence of the phenyl group. This rather large increase in bond length is not surprising, since it is known that the phenyl group is a very strong trans labilizing ligand (an approximate trans influence sequence is Cl < S < Sn, P < C, H < Si) due to its high σ-donor strength. , Perhaps more interesting is how this strong σ-donor affects the Pt−Cl bond in case of the NNC complex. It is known that the cis influence for a specific ligand is usually much smaller than its trans influence. , It is therefore not surprising that the average Pt−Cl bond length of NNC is 2.312 Å and only 0.008 Å longer than that in the [Pt(terpy)Cl] + complex.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This bond length is therefore increased by approximately 0.113 Å through the trans labilizing influence of the phenyl group. This rather large increase in bond length is not surprising, since it is known that the phenyl group is a very strong trans labilizing ligand (an approximate trans influence sequence is Cl < S < Sn, P < C, H < Si) due to its high σ-donor strength. , Perhaps more interesting is how this strong σ-donor affects the Pt−Cl bond in case of the NNC complex. It is known that the cis influence for a specific ligand is usually much smaller than its trans influence. , It is therefore not surprising that the average Pt−Cl bond length of NNC is 2.312 Å and only 0.008 Å longer than that in the [Pt(terpy)Cl] + complex.…”
Section: Discussionmentioning
confidence: 91%
“…This rather large increase in bond length is not surprising, since it is known that the phenyl group is a very strong trans labilizing ligand (an approximate trans influence sequence is Cl < S < Sn, P < C, H < Si) due to its high σ-donor strength. 53,55 Perhaps more interesting is how this strong σ-donor affects the Pt-Cl bond in case of the NNC complex. It is known that the cis influence for a specific ligand is usually much smaller than its trans influence.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the possibility of a π donation from the bridging dithioxamide to the platinum d orbitals would require a CC double bond connecting the two NCS frames, as has already been observed in some dithiolene−platinum(II) complexes . A number of X-ray measurements performed on uncoordinated dithioxamides and their metal complexes 5-8,19,20 ,, have shown that the central C−C bond is always a single bond. The unique exception deals with a tertiary dithioxamide-chelated to an electron-rich metal fragment, in which the ligand is reduced in the dithiolenic form .…”
Section: Resultsmentioning
confidence: 89%
“…The synthesis of the methyl platinum complexes trans-[Pt(dmso)2ClMe] (2) and cis-[Pt(dmso)2Me2] (3) (dmso = dimethyl sulfoxide) was first reported by Eaborn and coworkers in 1979, [1,2] and described in more detail for 2 by Romeo and Monsù Scolaro two decades later (Scheme 1). [3] These complexes are suitable precursors for the preparation of a wide range of organoplatinum compounds by substitution of the labile dmso ligand with N-heterocyclic carbenes, [4,5] phosphanes, [6][7][8][9][10] thioxamides, [11,12] CN-chelates, [13][14][15][16] CNN- [17] or CNC-pincers, [18,19] N-, 3 S-, or P-chelates, [20] imines, [21] and other ligands. Other valuable [PtL2ClMe] and [PtL2Me2] precursors, typically 1,5-cyclooctadiene [22][23][24] or dimethyl sulfide complexes, [25] are prepared by methods that are less convenient due to the use of very reactive methylating reagents (Li, [24,25] Al, [22] or Mg [23]) or the involvement of synthetic steps that have to be carefully performed.…”
Section: Introductionmentioning
confidence: 99%